Excessive Weight Gain During Pregnancy: Association with the Risk of Preeclampsia and Gestational Diabetes Melitus - Visti Delvina; Hasnia; Zaida Mauludiyah; Suriyati; Ni Nyoman Murti (CV. Get Press Indonesia, 2025)
Weight gain during pregnancy is an important indicator that influences maternal and fetal health. Excessive gestational weight gain (EGWG) has been associated with an increased risk of obstetric complications, including preeclampsia and gestational diabetes. This study aims to analyze the relationship between excessive weight gain during pregnancy and the incidence of preeclampsia and gestational diabetes mellitus (GDM) in pregnant women in the third trimester at Dr. H. Koesnadi Bondowoso General Hospital. This study used an observational analytical design with a cross-sectional approach and involved 140 pregnant women selected through a purposive sampling technique. Data were obtained through structured interviews, anthropometric measurements, and medical records, then analyzed using the Chi-square test. The results showed a significant association between excessive weight gain and the incidence of preeclampsia (p = 0.012) and gestational diabetes (p = 0.004). Women who exceeded the recommended weight gain limits were at a higher risk of developing these complications compared to those with normal weight gain. These findings emphasize the importance of controlling weight gain through routine monitoring and nutritional education during pregnancy. In conclusion, excessive weight gain is an important risk factor that needs attention in antenatal care services to prevent serious complications in pregnant women.